A Novel Variant in CLCN7 Regulates the Coupling of Angiogenesis and Osteogenesis - Peng, Hui; He, Hong-Bo; Wen, Ting (Frontiers in Cell and Developmental Biology, 2020)
Autosomal dominant osteopetrosis type II (ADO II), characterized by increased bone mass and density, is caused by mutations in the chloride channel 7 (CLCN7) gene. In this study, a novel missense variant in CLCN7 (c.1678A>G; p.Met560Val) was identified in three symptomatic subjects and one carrier of a Chinses family with ADO II. Notably, bone formation markers including osteocalcin and total procollagen type N-terminal propeptide have increased or presented at the upper limit of the normal range in the three patients. Serum factors secreted by osteoclast lineage cells and affecting the CD31hiEMCNhi vessel formation, such as TRAP-5b, PDGF-BB, VEGF, SLIT3 had a higher expression in three ADO II subjects than in 15 healthy age-matched and sex-matched controls. Moreover, the conditioned medium was obtained from preosteoclast induced from the ADO II patients’ peripheral blood mononuclear cells. It was found to promote the CD31hiEMCNhi vessel formation of human microvascular endothelial cells as well as osteogenic differentiation of bone marrow-derived stem cells. Taken together, our finding revealed a novel CLCN7 variant associated with ADO II and suggested that the sclerotic bone was potentially associated with the increase of the CD31hiEMCNhi vessel formation and bone formation.